Развитие, иерархия и взаимодействие геоинформационных моделей в структуре наук о Земле - Пивняк, Г.Г.; Бусыгин, Б.С.; Коротенко, Г.М. (Видавничий дім "Академперіодика" НАН України, 2007)
The systematic approaches to the organization of a structure of the many-level processes of standardization of a simulation and a use of the geospatial information are considered and generalized. The sequence of stages and elements underlying the development, construction, and use of models of the geospatial data in geoscience and in various applications is analyzed.